Characterization of the western Caribbean Sea waters through in vivo chlorophyll fluorescence - Aguirre-Gómez, Raúl; Salmerón-García, Olivia (Revista Ciencias Marinas y Costeras, 2015)
This paper presents the characteristics of fluorescence for the Caribbean Sea. Hydrographic and fluorometric data were gathered at the upper mixed layer during an oceanographic campaign carried out in the summer of 2001, from the Yucatan Peninsula to Colombian waters. In vivo fluorescence profiles show a conspicuous subsurface chlorophyll maximum located at a depth of around 107 m. These profiles are characteristic of oligotrophic waters such as those of the western Caribbean Sea.